Design of Joint Position and Constellation Mapping Assisted DCSK Scheme Subject to Laplacian Impulsive Noise - Cai, Xiangming; Xu, Weikai; Wang, Lin; Chen, Guanrong (IEEE communications letters, 2022)
In this letter, a joint position and constellation mapping (JPCM) assisted differential chaos shift keying (JPCM-DCSK) scheme is proposed to address the problem of unreliable data transmission in the power line communication (PLC) channel subjected to Laplacian impulsive noise. The constellation states and time slot position patterns are integrated cooperatively, which enables JPCM-DCSK to transmit more information bits. An effective JPCM detection algorithm is proposed to recover the information bits. Moreover, the bit error rate (BER) expression of JPCM-DCSK is derived over a multipath PLC channel, which is verified by computer simulations. Comparisons of BER performances demonstrate that JPCM-DCSK outperforms its competitors by 2 dB to 6 dB gains.